2012
DOI: 10.2224/sbp.2012.40.6.933
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cheating Behavior: A Longitudinal Study with Chinese Business Students

Abstract: The theory of planned behavior (Ajzen, 1985) was applied to predict Chinese business students' cheating behavior. Chinese business students (N = 205; response rate, 77.6%) were surveyed at 2 time points separated by 1 month. Attitude, subjective norms, perceived behavioral control, cheating intention, and demographic information were recorded at Time 1, and self-reported subsequent cheating behavior was measured at Time 2. The results show that attitude, subjective norms, and perceived behavioral control were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
(56 reference statements)
2
9
0
Order By: Relevance
“…However, theory-driven research on academic dishonesty in China is also quite limited. The majority of the research discovered in the literature review was conducted in the United States (e.g., Beck & Ajzen, 1991; Camara et al, 2017; Cronan et al, 2018; Lonsdale, 2017; Scrimpshire et al, 2017; Stone et al, 2007, 2009, 2010; Yu et al, 2018), with few studies in the context of China mainland (Yang, 2012a; Zhang et al, 2018). Research has shown that TPB has a fairly strong explanatory power for dishonesty in American students, but it is less clear in China.…”
Section: Introductionmentioning
confidence: 99%
“…However, theory-driven research on academic dishonesty in China is also quite limited. The majority of the research discovered in the literature review was conducted in the United States (e.g., Beck & Ajzen, 1991; Camara et al, 2017; Cronan et al, 2018; Lonsdale, 2017; Scrimpshire et al, 2017; Stone et al, 2007, 2009, 2010; Yu et al, 2018), with few studies in the context of China mainland (Yang, 2012a; Zhang et al, 2018). Research has shown that TPB has a fairly strong explanatory power for dishonesty in American students, but it is less clear in China.…”
Section: Introductionmentioning
confidence: 99%
“…While the results show no influence of subjective norms on the performing of an action, norms still influence the likelihood of performing a behavior (Yang, 2012).…”
Section: Resultsmentioning
confidence: 61%
“…To provide more support showing the influence of attitudes and perceived behavioral control on intention to perform a behavior, Yang (2012), conducted a study on cheating behavior in business students which found attitudes, subjective norms, and perceived behavioral control to be positively associated with the intention to cheat and cheating behavior. Specifically, the noted that subjective norms could impact significantly on attitude and that perceived behavioral control had a direct effect on cheating behavior.…”
Section: Rqmentioning
confidence: 99%
“…The findings obtained from this research are examined, and it is seen that Model 5 can explain the cheating behaviour in the context of the TPB. Yang (2012), in his study with 205 Chinese students studying management, discussed the cheating behaviour with the TPB. According to the results of the study, it was found that attitude, subjective norms and perceived behavioural control are in a positive relationship with the intention to cheat and that the perceived behavioural control has a direct effect on the cheating behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Beck & Ajzen (1991), in their study, argued that the modified version of the TPB is the most effective model to explain the intention towards cheating. Yang (2012), in his study with 205 Chinese students studying management, discussed the cheating behaviour with the TPB, it was found that attitude, perceived behavioural control and subjective norms are in a positive connection with the intention to cheat and that the perceived behavioural control has a valid effect on the cheating behaviour.…”
Section: Introductionmentioning
confidence: 99%